Rekonstruksi Manajemen Berbasis Sekolah di Era Transformasi Digital: Integrasi Kepemimpinan Adaptif dan Teknologi Pendidikan - Fajri Dwiyama (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2026)
Digital transformation has brought about fundamental changes in educational governance, which require schools to adapt to more responsive, collaborative, and data-driven management models. School-Based Management (SBM) as a decentralized approach to education management is still relevant, but its implementation faces challenges when faced with the complexity of rapid and dynamic digital change. This article aims to examine the reconstruction of MBS in the era of digital transformation through the integration of adaptive leadership and educational technology as a unit of school governance strategies. This study uses a qualitative approach with a systematic literature study method on scientific publications, education policies, and good practice reports related to SBM, school leadership, and digital transformation in education. The analysis was carried out thematically to identify patterns, gaps, and integration opportunities between SBM principles, adaptive leadership characteristics, and the use of educational technology in the context of school governance. The results of the study show that the implementation of SBM in the digital era is still dominated by administrative approaches and the partial use of technology, so it has not been able to encourage comprehensive changes in school governance. The integration of adaptive leadership allows schools to respond to uncertainty, manage resistance to change, and build an organizational culture that supports innovation. Meanwhile, educational technology plays an enabler in strengthening data-based decision-making, transparency, and multi-stakeholder collaboration in the school ecosystem. The novelty of this article lies in the formulation of the SBM reconstruction framework that positions educational technology as a structural component of school organizations, not just a supporting instrument. This framework affirms that the success of school digital transformation is highly dependent on adaptive leadership capacity in managing change and ensuring technology contributes directly to strengthening school autonomy, participation, and accountability. These findings are expected to be a conceptual and practical reference for policy makers and school leaders in developing SBM that is relevant, sustainable, and oriented towards improving the quality of education